2014
DOI: 10.1055/s-0033-1360174
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Effect of Hypericin after Topical Application in the Ex Ovo Quail Chorioallantoic Membrane Model

Abstract: Photosensitizing properties of hypericin are well known, and the chicken chorioallantoic membrane has previously been used to test photodynamic effects of hypericin and other substances. In our study the photodynamic effect of hypericin in the ex ovo quail chorioallantoic membrane model was evaluated. Steady-state and time-resolved fluorescence spectroscopy of hypericin solution in PEG-400 and its mixture in PBS was performed to assess and characterize the process of aggregation and disaggregation of hypericin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…Subsequently, two types of reactions might take place; type I reaction, during which the photosensitizer reacts directly with the substrate -a cell membrane or a molecule, and type II reaction, where the photosensitizer in triplet state transfers energy directly to molecular oxygen to form the excited singlet oxygen forms. Both types trigger further reactions, which result in the production of ROS that are toxic to many cellular structures and macromolecules (DNA, lipids, enzymes) (Castano et al 2004;Karioti and Bilia 2010;Čavarga et al 2014). Mikeš et al (2009) previously reported that PDT depended on the type of the photosensitizer used, its intracellular localization, as well as the genetic and metabolic potential of the monitored cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, two types of reactions might take place; type I reaction, during which the photosensitizer reacts directly with the substrate -a cell membrane or a molecule, and type II reaction, where the photosensitizer in triplet state transfers energy directly to molecular oxygen to form the excited singlet oxygen forms. Both types trigger further reactions, which result in the production of ROS that are toxic to many cellular structures and macromolecules (DNA, lipids, enzymes) (Castano et al 2004;Karioti and Bilia 2010;Čavarga et al 2014). Mikeš et al (2009) previously reported that PDT depended on the type of the photosensitizer used, its intracellular localization, as well as the genetic and metabolic potential of the monitored cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The PS could be applied intraperitoneally [ 134 ], topically [ 135 ], or intravascularly [ 133 , 134 , 136 , 137 , 138 , 139 ]. As many PSs are hydrophobic, quickly accessible vascularity enables us to analyze novel carriers, such as liposomes [ 30 , 139 ], solvents, e.g., N-methyl pyrrolidone [ 32 ], polyether compounds, such as polyethylene glycol [ 34 ], or liposomal nanoparticles [ 139 ]. The effects of PDT on normal vasculature of avian embryo with the utilization of different PSs, such as VT [ 140 , 141 ], BPD-MA, and mTHPP [ 142 ] or HY [ 34 ], have also been analyzed.…”
Section: Chorioallantoic Membrane Of Avian Embryo (Cam)mentioning
confidence: 99%
“…Moreover, an appreciable effort has been dedicated to a PDT study as a combined therapeutic approach with multiple antiangiogenic agents utilized [ 15 , 17 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Furthermore, a considerable effort has been focused on novel carriers, such as liposomes [ 30 , 31 ], dipolar solvents, e.g., N-methyl-pyrrolidone [ 32 , 33 ], polyether compounds, e.g., polyethylene glycol (PEG) [ 34 ], cyclodextrins [ 35 ], or nanoparticles [ 31 ]. We assumed that all these novel approaches could represent a potential solution for a PDT improvement in relation to tumor angiogenic mechanism inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Avian chorioallantoic membrane (CAM) has been used for the study of tumour angiogenesis and antivascular therapy. More frequent is chicken CAM model, however, Japanese quail (Coturnix japonica) CAM has also been successfully used (Vargas et al 2007;Čavarga et al 2014;Nowak-Sliwinska et al 2014). The CAM contains primarily type IV collagen, similar to the basement membrane of human oral epithelium (Rowe et al 2009).…”
Section: Introductionmentioning
confidence: 99%